تَنبِيهُ العَطْشَانِ عَلَى مَوْرِدِ الظَّمْآنِ لأبِي عليٍّ حُسَيْنِ بْنِ عليِّ بنِ طَلْحَةَ الرَّجْرَاجِيِّ الشَّوْشَاوِيِّ ت 899 هـ )بَابُ المَوْصُولِ( -دِرَاسَةً وَتَحْقِيقا- - مشري حليمة (University of Eloued جامعة الوادي, 2024)
"يتناول هذا البحث الموسوم بـ: ""تنبيه العطشان على مورد الظّمآن للإمام الرّجراجيّ -باب الموصول- (دِرَاسَةً وتحقيقاً)"" تحقيق أحد أهم شروح المغاربة لمنظومة مورد الظّمآن في علم الرّسم؛ لذا أردتُّ من خلال هذا البحث تحقيق جزء من هذه الموسوعة، ومحاولة الإجابة عن الإشكال الآتي: ما هي القيمة العِلْميّة لشرح الإمام الرّجراجيّ على مورد الظّمآن للإمام الخرّاز من خلال –باب الموصول-؟ وللإجابة على هذه الإشكال قسَّمتُ العمل إلى مبحثين: المبحث الأول سـمّيتُه بقسم الدّراسة تناولت فيه التّعريف بالنّاظم ونظمه وعرّفت بالرّسم وأبوابه والشّارح وشرحه وبالمقطوع والموصول وفوائده ثمّ بالنّسخ المعتمَدة، والمبحث الثاني سـمّيته بقسم التّحقيق وفيه قمت بتحقيق نصّ الكتاب في الجزء المراد منه وهو باب الموصول تحقيقا علميا. وخلُصتُ إلى عدّة نتائج من أهمّها: أنّ الإمام الرّجراجيّ اعتمد في كتابه تنبيه العطشان على أمّهات كتب أصول الرّسم كالمقنع للإمام الدّاني ومختصر التّبيين لأبي داود والمنصف للبلنسيّ، ومن أهمّ التّوصيات جمعُ استدراكات وتعقبات الإمام الرّجراجيّ على الإمام الخرّاز من خلال _باب الموصول_ وتحقيقها تحقيقًا علميًا. " This research , entitled Alerting the Thirty to the Source of Assurance by Imam al- Ragragi – in the Chapter of Connected Narrations, is discussed. An investigation into one of the most important explanations by Moroccan scholars of the book of Mawrid al –Dhamaan in the science of Calligraphy ilm al- Rasm. So through this research, I aimed to investigate a portion of this encyclopedia. And trying to answer the following issue: The scientific value of Imam al-Ragragi s explanation of Mawrid al-Dhaman by Imam al-Khurraz regarding the Chapter of by Connected Narrations. To answer these questions, Idevided the work into two sections: the first section, titled Study Value addressed the definition of the writer, his composition , the definition of Calligraphy and its chapters, the commentator and his commentary. The concepts of disconnected and connected narrations, their benefits and the adopted copies. The second section, titled Investigation Section focused on verifying the text of the book in the desired part which is the chapter of Connected Narrations, through scientific investigation. I concluded several important results, among which is that Imam al-Ragragi relied in his book Tanbih al-Atshan on the foundational books of Calligraphy, such as Al-Muqni by Imam al-Dani, Mukhtasar al-Tabyin by Abu Dawood, and Al-Mansuf by al-Balansi. One of the most important recommendations is collecting Imam Al_Rajraji 's comments on Imam Al_Kharaz through the chapter on the subject of connected narrations and verifyingthem scientifically.
Keywords: الرسم القرآني – باب الموصول.; Qur’anic drawing - chapter connected.